First report on black spot disease of Phyllanthus emblica L. fruits caused by Thielaviopsis paradoxa in Bangladesh - Sikder, MM; Ahmmed, MS; Sultana, A; Alam, N (International Journal of Agricultural Research, Innovation and Technology, 2021)
Fruit spot disease of Phyllanthus emblica L. is one of theproblems, which reduce the quality of the fruits at pre-harvest period. Fungal pathogen was isolated using tissue planting methods during November 2016 to December 2017. The fungus, Thielaviopsis paradoxa was identified using both morphological and molecular characterization based on internal transcribe spacer (ITS) region of ribosomal DNA (rDNA). Mycelial growth of the isolated fungus was evaluated on six different fungal culture media viz, potato sucrose agar (PSA), Richard agar (RA), carrot agar (CA), potato dextrose agar (PDA), honey peptone agar (HPA) and Hansen’s agar (HA) in which RA and HPA media provided the utmost growth. The optimum temperature of the fungus was recorded at 25 to 35ºC. Alternate cycle of 12h/12h light dark and neutral to basic pH was preferred by the studied fungus. Aqueous crude extracts of three plants (garlic, black cumin, and turmeric) were evaluated against the isolated fungus in which the highest inhibition was recorded due to garlic extract. Two food preservatives (sodium benzoate and vinegar) were also tested in which sodium benzoate (100 mM) was most efficient for the inhibition of T. paradoxa. Therefore, garlic and food preservative-sodium benzoate could be used to control this fungal growth associated with amla fruits. To the best of our knowledge, occurrence of T. paradoxa on amla fruits is a new record in Bangladesh. Int. J. Agril. Res. Innov. Tech. 10(2): 38-46, December 2020